Casting the net - connecting auxin signaling to the plant genome - Ma, Yanfei; Wolf, Sebastian; Lohmann, Jan U. (Cold Spring Harbor perspectives in biology, 2021)
Auxin represents one of the most potent and most versatile hormonal signals in the plant kingdom. Built on a simple core of only a few dedicated components, the auxin signaling system plays important roles for diverse aspects of plant development, physiology, and defense. Key to the diversity of context-dependent functional outputs generated by cells in response to this small molecule are gene duplication events and sub-functionalization of signaling components on the one hand, and a deep embedding of the auxin signaling system into complex regulatory networks on the other hand. Together, these evolutionary innovations provide the mechanisms to allow each cell to display a highly specific auxin response that suits its individual requirements. In this review, we discuss the regulatory networks connecting auxin with a large number of diverse pathways at all relevant levels of the signaling system ranging from biosynthesis to transcriptional response.